Multi-band gap-coupled microstrip patch antenna - Mi, Siya (2013)
The antennas of mobile devices are now designed to be able to work in multiple modes. In this paper, we propose a triband antenna with gap-coupled microstrip patch which can be used for GSM (900MHz), DSC1800 (1800MHz) and GPS system (1575MHz). The size of the antenna is controlled to be in the same scale as the conventional mictrostrip patch antenna. A parametric study was conducted to investigate the influences of various structural parameters on the antenna performance while maintaining the patch size.